Análise in silico, in vitro e in vivo de compostos organocalcogênios como possíveis anti-inflamatórios - Baptistini, Natália (Universidade Federal de São Carlos, 2015)
In this work are presented the in silico study of the formation of complexes between organochalcogens compounds with enzymes COX-1 and COX-2 that were carried out in order to study their potential to act as selective inhibitors of COX-2 and thus as anti-inflammatories, as well as the results of in vitro and in vivo experiments of this activity. There were modeled and studied 15 organochalcogens compounds and their enantiomers, with a structure similar to that of the selective drug celecoxib. Compounds 2-(phenylseleno)-2-(2-ethyl-X)acetophenones-4’Y-substituted , with Y = H, Br, CH3, OCH3, NO2 and X = SO2, SO, S, were modeled using as starting point the crystallographic structure of the compound with Y = Br and X = SO. The three dimensional structures of the COX-1 and COX-2 enzymes were obtained from the PDB. The results of the molecular docking calculations were evaluated considering the patterns of orientations/conformations, intermolecular interactions, π interactions and scores. The results of these experiments allowed to propose a mechanism of action as well as a preferred bonding mode that would explain the activity of these compounds as possible inhibitors of COX-2, which is a condition necessary to act as anti-inflammatory. In particular, the compound where Y = OCH3 and X = SO2 (5-OCH3) being selective to COX-2 is the one with the best chances to act as an anti-inflammatory. This is because the OCH3 substituent occupied the S1 subsite of the enzyme, maintaining the interaction with His90 and the SO2 moiety interacts with the Tyr355, an important amino acid for the metabolism of the COX-2 substrate, the arachidonic acid. The other interactions made by the compound, such as π interactions, are important for fixing the ligand in the active site, although they are not directly related to its selectivity. The experiments in vitro and in vivo confirm the in silico results, as the enzyme immunoassay showed that this compound exhibits greater inhibition of COX-2 relative to COX-1. Furthermore, the activity of the 5-OCH3 compound was evaluated with the classical models of edema formation, that is the carrageenan and zymosan induced inflammation in the rat paw, resulting in a significant reduction in paw thickness after two hours and decreasing of the temperature after one hour of the application of the anti-inflammatory agent. As the best results were obtained for the model of paw edema elicited by carrageenan this suggests that the compound acts better in the case of acute inflammation.
Keywords: COX-2; Organocalchogens; Molecular docking; Antiinflamatories; Biotecnologia; Ciclooxigenase; Anti-inflamatório; Docking molecular; Organocalcogênios; OUTROS::CIENCIAS